2011
DOI: 10.1007/s00059-011-3512-x
|View full text |Cite
|
Sign up to set email alerts
|

Deutsches Register für akute Aortendissektion Typ A (GERAADA)

Abstract: A European Registry of Aortic Diseases ("EuRADa") is being established this year under the leadership of the "Vascular Domain" of the European Association for Cardio-Thoracic Surgery (EACTS). This database will collect parameters on all aortic diseases, dissection types A and B, aneurysms, perforating ulcer (PAU), intramural wall hematoma (IMH), traumatic aortic ruptures, and all potential treatment strategies (medical treatment, open surgical and endovascular).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…In previous studies, complicated preoperative conditions, such as the presence of hemodynamic instability, requirement for cardiopulmonary resuscitation (CPR), end-organ malperfusion, and haemopericardium with cardiac tamponade, were recognized as adverse factors for surgical outcomes of ATAAD patients 1 4 . Among these high-risk patients, the in-hospital mortality rates were reported to be 36–54%, which was approximately twice that of the majority of ATAAD population 5 , 6 . Those with uncomplicated ATAAD comprise a relatively stable subgroup; however, their characteristics and surgical results seem underreported.…”
Section: Introductionmentioning
confidence: 96%
“…In previous studies, complicated preoperative conditions, such as the presence of hemodynamic instability, requirement for cardiopulmonary resuscitation (CPR), end-organ malperfusion, and haemopericardium with cardiac tamponade, were recognized as adverse factors for surgical outcomes of ATAAD patients 1 4 . Among these high-risk patients, the in-hospital mortality rates were reported to be 36–54%, which was approximately twice that of the majority of ATAAD population 5 , 6 . Those with uncomplicated ATAAD comprise a relatively stable subgroup; however, their characteristics and surgical results seem underreported.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies reported that the incidence of preoperative CPR ranges from 3.8% to 6.3% [ 1 3 ]. Among these patients, the in-hospital mortality rates ranged from 50% to 95% [ 1 , 4 , 5 ], which was approximately five-times to six-times higher than that of the general ATAAD population [ 6 , 7 ]. However, even though they comprise an extremely high-risk subgroup, the clinical characteristics and surgical results of patients with ATAAD undergoing preoperative CPR may be under-reported.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advancements in diagnostic tools, management algorithms, and surgical techniques in the past decades, ATAAD remains challenging for cardiothoracic surgeons. The in-hospital mortality rates ranged from 18% to 25% according to the international registry of acute aortic dissection, and have been reported as 17% by the German registry for acute aortic dissection type A [1, 2]. It is vital to use fast and safe arterial inflow to establish effective cardiopulmonary bypass (CPB) and avoid malperfusion in patients undergoing surgery for ATAAD.…”
Section: Introductionmentioning
confidence: 99%